The Photoshop CS2 speed clinic : automating Photoshop to get twice the work done in half the time - Kloskowski, Matt (Peachpit Press, 2006)
If you're looking for an easy way to work fast in Photoshop CS2, congratulations, you've found it! Matt Kloskowski, Education and Curriculum Developer for the NAPP, shows you how to use the power of automation to instantly save time, money, and frustration. Once you master these powerful tools, you'll wonder how you ever got along without them. You'll learn how to: • Effectively use Adobe Bridge to manage your images • Add automation using actions • Create smarter actions • Use batch processing • Speed up the Camera Raw workflow • Customize scripts • Fine tune filters and preferences • And much more! This guide is not only packed with info, it will also show you hidden actions and automation gems that are already loaded when you install Photoshop CS2! If you want to increase your speed, and get twice the work done with half the headaches--this is the book for you!